Building a Visual Test for Kindergartens’ children (Journal of the College of Education for Women, 2019)
The present research aimed to test the imagination of children, and may build sample consisted of (400) a baby and child, selected by random way of four Directorates (first Resafe, second Resafe ,first alkarkh , second alkarkh), in order to achieve the objective of research the tow researchers have a test of imagination and extract the virtual and honesty plants distinguish paragraphs and paragraphs and difficulty factor became the test consists of (32), statistical methods were used (Pearson correlation coefficient, coefficient of difficult passages, highlight paragraphs, correlation equation, an equation wrong Standard) the tow researchers have a number of recommendations and proposals.